Without using trigonometric tables, evaluate the following:
sin 72°cos 18°−sec 32°cosec 58°\dfrac{\text{sin 72°}}{\text{cos 18°}} - \dfrac{\text{sec 32°}}{\text{cosec 58°}}cos 18°sin 72°−cosec 58°sec 32°
4 Likes
Solving,
⇒sin 72°cos 18°−sec 32°cosec 58°⇒sin (90° - 18°)cos 18°−sec 32°cosec (90° - 32°)As, cosec (90 - θ) = sec θ and sin (90 - θ) = cos θ⇒cos 18°cos 18°−sec 32°sec 32°⇒1−1⇒0.\Rightarrow \dfrac{\text{sin 72°}}{\text{cos 18°}} - \dfrac{\text{sec 32°}}{\text{cosec 58°}} \\[1em] \Rightarrow \dfrac{\text{sin (90° - 18°)}}{\text{cos 18°}} - \dfrac{\text{sec 32°}}{\text{cosec (90° - 32°)}} \\[1em] \text{As, cosec (90 - θ) = sec θ and sin (90 - θ) = cos θ} \\[1em] \Rightarrow \dfrac{\text{cos 18°}}{\text{cos 18°}} - \dfrac{\text{sec 32°}}{\text{sec 32°}} \\[1em] \Rightarrow 1 - 1 \\[1em] \Rightarrow 0.⇒cos 18°sin 72°−cosec 58°sec 32°⇒cos 18°sin (90° - 18°)−cosec (90° - 32°)sec 32°As, cosec (90 - θ) = sec θ and sin (90 - θ) = cos θ⇒cos 18°cos 18°−sec 32°sec 32°⇒1−1⇒0.
Hence, sin 72°cos 18°−sec 32°cosec 58°=0.\dfrac{\text{sin 72°}}{\text{cos 18°}} - \dfrac{\text{sec 32°}}{\text{cosec 58°}} = 0.cos 18°sin 72°−cosec 58°sec 32°=0.
Answered By
2 Likes
cot 40°tan 50°−12(cos 35°sin 55°)\dfrac{\text{cot 40°}}{\text{tan 50°}} - \dfrac{1}{2}\Big(\dfrac{\text{cos 35°}}{\text{sin 55°}}\Big)tan 50°cot 40°−21(sin 55°cos 35°)
(sin 49°cos 41°)2+(cos 41°sin 49°)2\Big(\dfrac{\text{sin 49°}}{\text{cos 41°}}\Big)^2 + \Big(\dfrac{\text{cos 41°}}{\text{sin 49°}}\Big)^2(cos 41°sin 49°)2+(sin 49°cos 41°)2
cos 75°sin 15°+sin 12°cos 78°−cos 18°sin 72°\dfrac{\text{cos 75°}}{\text{sin 15°}} + \dfrac{\text{sin 12°}}{\text{cos 78°}} - \dfrac{\text{cos 18°}}{\text{sin 72°}}sin 15°cos 75°+cos 78°sin 12°−sin 72°cos 18°
sin 25°sec 65°+cos 25°cosec 65°\dfrac{\text{sin 25°}}{\text{sec 65°}} + \dfrac{\text{cos 25°}}{\text{cosec 65°}}sec 65°sin 25°+cosec 65°cos 25°.